The differences between Peirce and Russell’s thought on Philosophy, Mathematics and Logic - Saran, Lucas Antonio (2021)
The goal of this work will consist in, in a specific angle, exposing and comparing the thought of Charles Sanders Peirce and Bertrand Russell: we will compare the conceptions of Peirce and Russell on philosophy, mathematics and logic. This comparative exposition will have the goal of showing and highlighting the differences between the two authors herein studied (Peirce and Russell). With this goal in sight, we divide this work into two sections: in the first section, exclusively discussing Peirce and presenting a short exposition of his conceptions of philosophy, mathematics and a few elements of logic; in the second section, we will discuss Russell in the subjects of philosophy, mathematics and logic, noting that, still within this second section, we will make a comparison between the ideas of Peirce and Russell for each addressed subject.